Exploratory Ingestions of Novel Anticoagulants and Antiplatelets: What Is the Risk?. Issue 6 (June 2020) - Levine, Michael; Pizon, Anthony; Beuhler, Michael; Cantrell, F. Lee; LoVecchio, Frank; Spyres, Meghan; Skolnik, Aaron B.; Brooks, Daniel E.
Abstract : Background: Historically, anticoagulants and antiplatelet agents included warfarin and aspirin, respectively. In recent years, numerous novel anticoagulants (eg, direct thrombin inhibitors and factor Xa inhibitors) as well as the adenosine diphosphate receptor antagonists have increased significantly. Little information on the bleeding risk after exploratory ingestion of these agents is available. The primary purpose of this study is to evaluate the bleeding risk of these agents after an exploratory ingestion in children 6 years or younger. Methods: This retrospective multicenter poison control center study was conducted on calls between 2005 and 2014. The following agents were included: apixaban, clopidogrel, dabigatran, edoxaban, prasugrel, rivaroxaban, or ticagrelor. Bleeding characteristics and treatment rendered were recorded. Results: A total of 638 cases were identified. Most cases involved antiplatelet agents. No patient developed any bleeding complication. The administration of charcoal was independent of the amount of drug ingested. Conclusion: Accidental, exploratory ingestions of these agents seem well tolerated, with no patient developing bleeding complications.